The Corelation between Family Support and Depression in the Elderly in the Work Area of the Bangetayu Health Center, Semarang - Muslikhatul Khoiriyah; Moch. Aspin; Iskim Luthfa; Nutrisia Nu’im Haiya (Universitas Islam Sultan Agung, 2023)
Elderly experiencing physical and psychological problems. The physical problem faced by the elderly is the decreased ability to perform daily activities independently including spiritual activities. Psychological problems such as loneliness and anxiety over death that result in depression. The purpose of this study was to analyze the relationship between family support and depression in the elderly in the work area of the Bangetayu Public Health Center in Semarang. This research design uses correlation study research with cross sectional approach. The population in this study were all the elderly who lived in the work area of the Bangetayu Public Health Center, namely 637 elderlies. The sampling technique used was simple random sampling with 86 respondents. The results showed that the majority of family support was in the moderate category (75.6%), and most of the elderly also experienced depression in the moderate category (89.5%). Statistical test results show that there is a significant corelation between family support and elderly depression. Based on the above results, the family with the elderly to continue to give attention, affection, and other forms of support to the elderly so they can live the rest of their lives happily.